Lexical and Semantic Group of Verbs Denoting Scents in the Corresponding Lexical and Semantic Field (as presented at the Dictionary of Russian Folk Dialects) - T I Rusenko (RUDN Journal of Language Studies, Semiotics and Semantics, 2014)
The article is devoted to the evaluation of verbs contained in the Dictionary of Russian Folk Dialects and referring to scents. The aim of the research is to distinguish the lexical-semantic group of the verbs that refer to scents as well as to define their place in the relevant lexical-semantic field.